BETWEEN ROA, ROE, NPM, AND EBIT VARIABLES, WHICH CAN CHANGE THE STOCK PRICE - Suroso, Sugeng (SEAN Institute, 2021)
Financial accounting information is general purpose information presented in accordance with Generally Accepted Accounting Principles (GAAP). This information is used for internal and external parties. Accounting information related to company performance is the most basic requirement in the decision-making process for investors in the capital market. Stock prices in accounting information presented in the IDX's financial statements, also present the state of ROA, ROE, NPM and EBIT. The purpose of this study was to determine the effect of accounting information on stock prices of manufacturing companies in the food and beverage sub-sector on the Indonesia Stock Exchange. This research is located at the IDX (Indonesia Stock Exchange) office. The sample selection method in this research is purposive sampling method with a total sample of 5 companies. The data collection techniques collect data on the company's financial statements during the study period. The data analysis method used is multiple regression with the help of SPSS software. The results showed that 1) the coefficient value of ROA, ROE, NPM, and EBIT showed the effect on stock prices simultaneously. 2) ROA, ROE, NPM partially significant effect on stock prices, while EBIT has no influence on the stock prices of manufacturing companies in the food and beverage sub-sector on the IDX. 3) The most dominant variable influencing ROA, ROE, NPM and EBIT on the share prices of food and beverage sub-sector manufacturing companies on the IDX is the ROA variable.